Odpowiedź :
[tex]a) \ f(x) = \frac{6}{x-4}, \ \ P(2, -4)\\\\L = -4\\\\P = \frac{6}{2-4} = \frac{6}{-2} = -3\\\\L\neq P, \ \ NIE[/tex]
[tex]b) \ f(x) = \frac{3}{x+2}, \ \ P(4, \frac{1}{2})\\\\L = \frac{1}{2}\\\\P = \frac{3}{4+2} = \frac{3}{6} = \frac{1}{2}\\\\L = P, \ \ TAK[/tex]
[tex]c) \ f(x) = \frac{3}{x-1}, \ \ P(\frac{1}{2}, -\frac{3}{2})\\\\L = -\frac{3}{2}\\\\P = \frac{3}{\frac{1}{2}-1} =\frac{3}{-\frac{1}{2}} = -6\\\\L \neq P, \ \ NIE[/tex]
[tex]d) \ f(x) = \frac{0,5}{x+4}, \ \ P(-6, -\frac{1}{4})\\\\L = -\frac{1}{4}\\\\P = \frac{0,5}{-6+4} = \frac{0,5}{-2} = -\frac{1}{4}\\\\L = P, \ \ TAK[/tex]
a) f(x)=6/(x-4) , P=(2,-4)
f(2)=6/(-2-4)=6/(-6)=-1
-1 ≠ -4
Nie.
b) f(x)=3/(x+2) , P=(4,1/2)
f(4)=3/(4+2)=3/6=1/2
1/2 = 1/2
Tak.
c) f(x)=3/(x-1) , P=(1/2,-3/2)
f(1/2)=3/(1/2-1)=3/(-1/2)=-6
-6 ≠ -3/2
Nie.
d) f(x)=0,5/(x+4) , P=(-6,-1/4)
f(-6)=0,5/(-6+4)=0,5/(-2)=-1/4
-1/4 = -1/4
Tak.